Rubio Angulo, J. (1984). Hermenéutica y Ciencias Humanas. Colección Cuadernos de Cátedra, No. 1, Facultad de Filosofía, Universidad Javeriana, Bogotá. 218 págs. - Hoyos-Vásquez S.J., Jaime; Pontificia Universidad Javeriana (2016)
null